2007
DOI: 10.1002/bit.21502
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the biochemical activity of full‐scale enhanced biological phosphorus removal systems: A comparison with metabolic models

Abstract: The metabolism of polyphosphate accumulating organisms (PAOs) has been widely studied through the use of lab-scale enrichments. Various metabolic models have been formulated, based on the results from lab-scale experiments using enriched PAO cultures. A comparison between the anaerobic stoichiometry predicted by metabolic models with that exhibited by full-scale sludge in enhanced biological phosphorus removal (EBPR) wastewater treatment plants (WWTPs) was performed in this study. Batch experiments were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…In the Netherlands, Accumulibacter abundance (5.7–16.4% in seven EBPR plants) was correlated to a well‐defined denitrification stage and high pHs in the anaerobic zone (López‐Vázquez et al ., 2008). In Australia, Accumulibacter were present at 7–12% of total bacteria in four facilities examined by Saunders and colleagues (2003), and 5–10% in two facilities studied by Pijuan and colleagues (2008). However, another survey conducted on nine treatments plants in the eastern states of Australia showed that Accumulibacter were rare in most facilities, and instead Actinobacteria may have been the primary PAOs (Beer et al ., 2006).…”
Section: Ecological Distribution In Ebpr Systemsmentioning
confidence: 96%
“…In the Netherlands, Accumulibacter abundance (5.7–16.4% in seven EBPR plants) was correlated to a well‐defined denitrification stage and high pHs in the anaerobic zone (López‐Vázquez et al ., 2008). In Australia, Accumulibacter were present at 7–12% of total bacteria in four facilities examined by Saunders and colleagues (2003), and 5–10% in two facilities studied by Pijuan and colleagues (2008). However, another survey conducted on nine treatments plants in the eastern states of Australia showed that Accumulibacter were rare in most facilities, and instead Actinobacteria may have been the primary PAOs (Beer et al ., 2006).…”
Section: Ecological Distribution In Ebpr Systemsmentioning
confidence: 96%
“…By comparing the anaerobic stoichiometry from fullscale EBPR wastewater treatment plants with the predictive models from previous researchers, Pijuan et al (2008) suggested that metabolic models should incorporate glycogen degradation and the TCA cycle for the production of reducing power in PAOs when acetate is used as the substrate. They also proposed that the contribution of the TCA cycle to the anaerobic production of reducing power was very low or negligible when propionate was used as carbon source.…”
Section: Evidence For Both Modelsmentioning
confidence: 99%
“…Phosphorus removal via biological processes is more economical and environmentally sustainable compared to traditional (chemical) phosphorus removal processes for a number of reasons, including chemical costs, the ability to subsequently release and recover phosphorus, and plantavailability of phosphorus where waste activated sludge (WAS) is used directly (Shu et al, 2006). So far, Bio-P removal processes have been widely applied to treat domestic wastewater (<10 mg P L -1 in influent) (Pijuan et al, 2008), abattoir wastewater (20-40 mg P L -1 ) (Lemaire et al, 2009), and high-strength industrial wastewater (60-100 mg P L -1 ) (Broughton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%